EFEK ANTIINFLAMASI KOMBINASI ASTAXANTHIN DENGAN VITAMIN E TERHADAP KADAR C-REACTIVE PROTEIN (CRP): Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan - Saskia Febrian Dwi Putri; Sampurna (PT. Hasba Edukasi Mandiri, 2026)
Inflammation is a protective immune system response to tissue damage that can trigger increased levels of C-Reactive Protein (CRP), a marker of acute annd chronic inflammation. Carrageenan is known as an inflammatory agent that induces CRP production through activation of the Toll-Like Receptor-4 (TLR-4) and Nuclear Factor Kappa-β (NF-κB) pathways. Astaxanthin and vitamin E have potential antiinflammatory effects by inhibiting NF-κB and ROS. This study aims to determine the effect of the combination of astaxanthin with vitamin E on CRP levels in male white Wistar rats fed on carrageenan. This type of experimental research used a “post-test only control group design” with 30 male white Wistar rats randomly divided into 3 groups. KN (normal control) was given a standard feed diet, KS (negative control) with 1% carrageenan induction and KP (treatment group) was given a combination of astaxanthin 0,72 mg/kgBW and vitamin E 24,1 mg/kgBW with 1% carrageenan induction. CRP levels were measured using the ELISA method and analyzed by the Shapiro Wilk test, Levene test, One Way ANOVA, and Post Hoc LSD. The average percentage of CRP levels in KN was (0,75 ng/mL), KS (2,35 ng/mL) and KP (1,01 ng/mL) which means KS experienced a significant increase in CRP levels (p<0,05) compared to KN. Statistical tests showed that the data were normally distributed and homogeneous (p>0,05), and there were significant differences between the three groups (p<0,05). The conclusion of this study is that there is an anti-inflammatory effect of the combination of astaxanthin with vitamin E on C-Reactive Protein (CRP) levels in male Wistar rats induced by 1% carrageenan.